PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PILAR TAX BERBASIS WEBSITE MENGGUNAKAN SMART APPS CREATOR PADA ELEMEN PERPAJAKAN - Haliza, Nur; Pratiwi, Vivi (STKIP Persada Khatulistiwa Sintang, 2024)
This research was carried out with the aim of describing the media development process, the suitability of the media and students' responses regarding the use of the learning media developed, namely interactive learning media based on website using SAC (Smart Apps Creator) on TAX elements for class XI. This interactive learning media is called PILAR TAX (Smart in Learning taxes). This research uses the ADDIE development model including analysis, design, development, Implementation, dan evaluation. Stesting objects and application of media-based learning website is a class XI student in Financial and Institutional Accounting.Â The research results show that the development of interactive learning media is based on website on the tax element, the assessment from material experts was 91.8% in the